Incidence of hepatitis B virus infection in young Chinese blood donors born after mandatory implementation of neonatal hepatitis B vaccination nationwide. Issue 9 (2nd May 2018) - Tang, X.; Allain, J.‐P.; Wang, H.; Rong, X.; Chen, J.; Huang, K.; Xu, R.; Wang, M.; Huang, J.; Liao, Q.; Shan, Z.; Luo, S.; et al.
Summary: This study was carried out to determine the incidence of hepatitis B virus (HBV) infection in the young generation born after mandatory implementation of hepatitis B vaccination since 1992. Repeat blood donors born between 1992 and 1997 were enrolled, who gave blood at least twice during the past 3 years. Donors were tested for HBV infection markers of HBsAg, anti‐HBc, anti‐HBs and viral DNA by immunoassays (EIAs) and nucleic acid tests (NAT). A total of 14 937 pre‐donation screening qualified young repeat donors aged 18‐23 years were tested with 9 (0.06%) being HBsAg by EIA and 10 (1:1494) HBV DNA positive by Ultrio NAT (10.4 IU/mL), respectively. HBV DNA was further detected in 1:192 (9/1732) anti‐HBc+ repeat donors with Ultrio Plus NAT (3.4 IU/mL). Most cases were identified as occult HBV infection (OBI). Of 14 937 repeat donors, 20.9% were anti‐HBc+ positive, while approximately 50% of 12 024 repeat donors were anti‐HBs negative or had levels <100 IU/L. HBsAg+ or OBI strains were classified as wild type of genotype B or genotype C. Incident HBV infection in repeat donors was approximately 1:18.5 person‐years (1.1%/year) but significantly less frequent in donors with confirmed HBV vaccination (2.4%‐3.3%) than those unsure of vaccination status (10.5%; P  =   .0023). Hepatitis B virus vaccination appears largely protective of HBV infection, but incidence of infections increases in young adults with mostly undetectable or low anti‐HBs or occasionally high anti‐HBs. A boost of hepatitis B vaccine for adolescents prior to age 18 years may reduce HBV infection, and implementation of more sensitive NAT in blood donation screening may improve HBV safety in blood transfusion.